SOSIALISASI SADAR WISATA BAGI SISWA SMA NEGERI 8 KEPULAUAN SULA - Asti Ayuningsih; Taghulihi, Betly (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This community service activity was conducted to address the need for increased tourism awareness among young people in potential tourist destinations. The activity consisted of a socialization program on tourism awareness held in SMA Negeri 8 Kepulauan Sula, Sula Islands Regency, North Maluku Province. The main objective of this activity was to introduce a sense of tourism awareness in youth, in line with the government initiatives. The activity included several stages, such as pre-test, concept of tourism awareness presentation, and post-test. The result of this activity indicated that students had gained a solid understanding of the tourism awareness concepts which was shared during the session. It is hoped that this awareness will be passed on to students at other schools in Sula Islands regency and, ultimately, to the wider community in a non-formal manner.